2012
DOI: 10.4161/chan.18916
|View full text |Cite
|
Sign up to set email alerts
|

Bimolecular fluorescence complementation and targeted biotinylation provide insight into the topology of the skeletal muscle Ca2+channel β1a subunit

Abstract: 2+ , calciumIn skeletal muscle, L-type calcium channels (DHPRs), localized to plasma membrane sarcoplasmic reticulum junctions, are tightly packed into groups of four termed tetrads. Here, we have used bimolecular fluorescence complementation (BiFC) and targeted biotinylation to probe the structure and organization of b1a subunits associated with native Ca V 1.1 in DHPRs of myotubes. The construct YN-b1a-YC, in which the non-fluorescent fragments of YFP ("YN" corresponding to YFP residues 1-158, and "YC" corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…The yellow fluorescence arising from the YFP tag was arrayed in double rows having a center-tocenter spacing of ϳ2 m, consistent with a T-tubular localization. Furthermore, the red fluorescence arising from the bound fluoro-gold streptavidin colocalized with the yellow fluorescence, indicating that there is effective biotinylation of the BAD attached to the ␤ 1a C terminus and that its disposition in triad junctions makes it accessible to a moderately sized (1 nm) probe, consistent with previous work on myotubes (34,45,46). This previous work also showed that EC coupling was not impaired when streptavidin bound to YFP-␤-BAD in myotubes (45).…”
Section: Resultssupporting
confidence: 78%
“…The yellow fluorescence arising from the YFP tag was arrayed in double rows having a center-tocenter spacing of ϳ2 m, consistent with a T-tubular localization. Furthermore, the red fluorescence arising from the bound fluoro-gold streptavidin colocalized with the yellow fluorescence, indicating that there is effective biotinylation of the BAD attached to the ␤ 1a C terminus and that its disposition in triad junctions makes it accessible to a moderately sized (1 nm) probe, consistent with previous work on myotubes (34,45,46). This previous work also showed that EC coupling was not impaired when streptavidin bound to YFP-␤-BAD in myotubes (45).…”
Section: Resultssupporting
confidence: 78%
“…Relevant to this issue, earlier experiments examined the spatial interrelationships of ␤ 1a subunits in DHPR tetrad arrays by analyzing constructs expressed in ␣ 1 null myotubes. These experiments failed to detect either intermolecular FRET (39) or bimolecular fluorescence complementation (40) between ␤ 1a subunits in adjacent DHPRs. Thus, it was suggested that the adjacent ␤ 1a subunits were separated from one another by Ͼ10 nm (see Fig.…”
Section: Discussionmentioning
confidence: 91%
“…8 in Ref. 40). If this suggested arrangement is correct, then the I-II loops of ␣ 1S also would likely be positioned at a distance Ͼ10 nm from the ␣ 1S cytoplasmic domains of adjacent DHPRs.…”
Section: Discussionmentioning
confidence: 99%
“…For clarity, the β 1a subunits are superimposed on the α 1S subunits, and the α 2 δ-1 subunits, γ 1 subunits, and other nonessential components of the junction have been omitted. The orientation of β 1a within the tetrad follows on previous work ( Leuranguer et al, 2006 ; Sheridan et al, 2012 ). In the right panels (B and C), we present two potential mechanisms by which Rem (black ovals) may disrupt EC coupling.…”
Section: Discussionmentioning
confidence: 96%